The effect of life events on NSSI: the chain mediating effect of sleep disturbances and PLEs among Chinese college students - Wang, Hongcai; Liu, Xianhua; Zeng, Zihao; Liu, Shuangjin; Yang, Qin; Qi, Qi; Wu, Tong; Hu, Yiqiu (Frontiers in Psychology, 2024)
This study aimed to explore the relationship between life events and non-suicidal self-injury (NSSI) in college students, as well as the mediating effect of sleep disturbances and psychotic-like experiences (PLEs). After excluding invalid questionnaires, 5,754 were retained, and the valid efficiency was 75.94%. The subjects were aged 16 to 29 years (M = 19.166; SD = 1.392), with 1,969 males (34.22%) and 3,785 females (65.78%). Life events, sleep disturbances, PLEs, and NSSI were assessed using standard scales. Data were analyzed by Pearson Correlation Analysis and bias-correction percentile Bootstrap method. The results show that (1) life events were significant positive predictors of NSSI, sleep disturbances, and PLEs; (2) sleep disturbances, PLEs, and the chain mediation between the two, were mediators between life events and NSSI. Life events are thus shown to be an important external factor influencing NSSI in university students, and this process is mediated through sleep disturbances, PLEs, and the chain between the two. Interventions for NSSI can therefore be made by improving college students’ sleep quality and reducing PLEs.